Influência do ciclo lunar na captura de Aedes scapularis (Diptera, Culicidae) na Mata Atlântica do Paraná Influence of the lunar cycle on the traping of Aedes scapularis (Diptera, Culicidae) in the Atlantic forest of Paraná - Adson Luís Sant'Ana; Ana Leuch Lozovei (Iheringia: Série Zoologia, 2001)
From October 1995 to January 1996 Aedes (Ochlerotatus) scapularis (Rondani, 1948) was studied in a small area of the Atlantic Forest, Serra do Marumbi, Morretes, Paraná, Brazil. Adults were captured with Shannon light traps for 48 nights, representing 12 nights for seven time intervals. Traps were operated from dusk to dawn. The influences on flight activity of the lunar phase, ambient temperature, relative humidity, and rainfall were analyzed. Ae. scapularis had a flight behaviour different in each of the four lunar phases. In relation to flight period, the species showed higher activity during the first three lunar intervals. Among the climatic variables, temperature and relative humidity positively influenced flight activity during the night.